2007
DOI: 10.1103/physrevlett.99.256801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bidirectional Charge Transfer and Molecular Distortions on the Electronic Structure of a Metal-Organic Interface

Abstract: Interface energetics are of fundamental importance in organic and molecular electronics. By combining complementary experimental techniques and first-principles calculations, we resolve the complex interplay among several interfacial phenomena that collectively determine the electronic structure of the strong electron acceptor tetrafluoro-tetracyanoquinodimethane chemisorbed on copper. The combination of adsorption-induced geometric distortion of the molecules, metal-to-molecule charge transfer, and molecule-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
284
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(303 citation statements)
references
References 30 publications
17
284
2
Order By: Relevance
“…ARTICLE already reported. 28,29 When coadsorbed with molecular donors, it reduces the hole-injection barrier between Au electrodes and several organic semiconductors. 30,31 We then consider the doubly substituted 2,5-difluoro-7,7,8,8-tetracyanoquinodimethane (F2-TCNQ, A = 4.59 eV) and fluoro-7,7,8,8-tetracyanoquinodimethane (F-TCNQ, A = 4.55 eV), where only one H is replaced (see the SI for the molecular structures on the substrate).…”
Section: Articlementioning
confidence: 99%
“…ARTICLE already reported. 28,29 When coadsorbed with molecular donors, it reduces the hole-injection barrier between Au electrodes and several organic semiconductors. 30,31 We then consider the doubly substituted 2,5-difluoro-7,7,8,8-tetracyanoquinodimethane (F2-TCNQ, A = 4.59 eV) and fluoro-7,7,8,8-tetracyanoquinodimethane (F-TCNQ, A = 4.55 eV), where only one H is replaced (see the SI for the molecular structures on the substrate).…”
Section: Articlementioning
confidence: 99%
“…Partitioning of the density of states (DOS) into contributions from individual molecular orbitals (MODOS) was performed in analogy to previous studies [41,42] using the atomic orbital-based SIESTA code [43]. For these calculations, the PBE xc functional and norm-conserving pseudopotential in the Troullier Martins scheme were adopted including linear core corrections.…”
Section: Methodsmentioning
confidence: 99%
“…In order to understand the electronic structure origination of these anomalies, we further study the phase stability of Nb at high pressure under various chemical environments. Charge-transfer at surface or interface could induce structural rearrangement, [55][56][57] and this electron accepting/donating will shift the Fermi level. Our previous study indeed found that the Fermi level has a remarkable impact on the phase stability of V. 18 By using the same method as employed in Ref.…”
Section: E Charge Transfer Induced Anomaliesmentioning
confidence: 99%